2006
DOI: 10.1530/eje.1.02092
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and bone turnover in young adult survivors of childhood acute lymphoblastic leukaemia

Abstract: Objective: Treatment for childhood leukaemia induces many risk factors for development of decreased bone mineral density (BMD). Physical activity is also known to affect BMD. The aim was to study BMD and markers of bone turnover in a well-defined group of survivors of acute lymphoblastic leukaemia (ALL) who had all reached final height as well as peak bone mass, taking both previous treatment and physical activity into consideration. Design: All patients treated for ALL before the onset of puberty in the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 44 publications
7
36
2
1
Order By: Relevance
“…In contrast with conventional ALL treatment, all patients had also received TBI, which might induce endocrine deficits, such as impaired GH secretion and hypogonadism in girls, and might also have direct effects on the BM stroma. 1,2 Jarfelt et al 22 found a low bone mass in 10 of 35 young Swedish adult survivors (29%) with a median follow-up of 20 years after conventional ALL therapy, that is, a prevalence commensurate with that observed in our transplanted patients. On the other hand, 54% of their patients had received cranial radiation therapy, which might induce impaired GH secretion and short stature, compared with 39% in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…In contrast with conventional ALL treatment, all patients had also received TBI, which might induce endocrine deficits, such as impaired GH secretion and hypogonadism in girls, and might also have direct effects on the BM stroma. 1,2 Jarfelt et al 22 found a low bone mass in 10 of 35 young Swedish adult survivors (29%) with a median follow-up of 20 years after conventional ALL therapy, that is, a prevalence commensurate with that observed in our transplanted patients. On the other hand, 54% of their patients had received cranial radiation therapy, which might induce impaired GH secretion and short stature, compared with 39% in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…Intensive multimodality treatments including cytotoxic agents, glucocorticoids and radiotherapy may have direct and indirect negative effects on bone metabolism [1,6,11,13,14,15,16,17,18]. Other factors implicated in bone loss include the cancer disease itself, poor nutrition, reduced exposure to sun, and decreased physical activity during and after treatment [7,19,20]. Ultimately, insufficient bone mass acquisition and/or accelerated loss during childhood and adolescence might predispose these patients to later osteoporosis and pathologic fractures [6,11,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This is notably confirmed by the fact that our controls with normal bone mass had received the same treatment. Others have also looked at bone markers in survivors [19][20][21][22] and have had the same results of no persisting abnormalities of bone mineral metabolism.…”
Section: Discussionmentioning
confidence: 91%